2019
DOI: 10.3389/fmicb.2019.01116
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Alterations in Yak Rumen Bacteria Community and Metabolome Characteristics in Response to Feed Type

Abstract: Current knowledge about the relationships between ruminal bacterial communities and metabolite profiles in the yak rumen is limited. This is due to differences in the nutritional and metabolic features between yak and other ordinary cattle combined with difficulties associated with farm-based research and a lack of technical guidance. A comprehensive analysis of the composition and alterations in ruminal metabolites is required to advance the development of modern yak husbandry. In the current study, we charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
164
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(212 citation statements)
references
References 96 publications
44
164
3
1
Order By: Relevance
“…The main metabolites were amino acids, peptides and analogues in this study, which was consistent with the previous reports [43,60]. Amino acids in the rumen are the key precursors for protein and polypeptides synthesis and are mainly obtained from the dietary proteins and microproteins [61].…”
Section: Comparison Of the Composition And Differences Of Ruminal Metsupporting
confidence: 92%
See 2 more Smart Citations
“…The main metabolites were amino acids, peptides and analogues in this study, which was consistent with the previous reports [43,60]. Amino acids in the rumen are the key precursors for protein and polypeptides synthesis and are mainly obtained from the dietary proteins and microproteins [61].…”
Section: Comparison Of the Composition And Differences Of Ruminal Metsupporting
confidence: 92%
“…In this study, 16S rRNA gene sequencing was used to assess the rumen bacterial community in SWCG. Liu et al [43] and Tapio et al [44] reported that the richness of the bacterial community were in uenced by diets. Our results also revealed low bacterial richness (ACE and Chao indices) with the increasing levels of dietary energy and protein, while no signi cant changes were detected in the bacterial diversity (Shannon and Simpson indices).…”
Section: Comparison Of the Composition And Differences Of Ruminal Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…Small Tail Han sheep, which originated from low land [18], later adapted to the grazing lifestyle on the Qinghai-Tibetan Plateau and became an indispensable species to the local life and economy [19]. Although a few studies have reported the rumen prokaryotic community from grazing yak, Tibetan sheep and Small Tail Han sheep [19][20][21][22][23], few studies have considered the rumen eukaryotic community composition of these three ruminant species, especially grazing under the same natural pasture. Thus, our prime aim of this study is to characterize the rumen fungal community of mainly grazing ruminant species (Yak, Tibetan sheep and Small Tail Han sheep) in the Qinghai-Tibetan Plateau, so as to identify the ruminal fungal strains that are prevalent in the rumen which may be associated with fiber degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The α-diversity of the gut microbiota in FMD samples was signi cantly different in two seasons, and the diversity lower in winter than in summer (Shannon index: p<0.05; Chao index: p<0.05); meanwhile, the diversity of the gut microbiota in SMD samples was not signi cantly different between seasons. Many studies have shown that a number of factors have an impact on gut microbial diversity, such as host healthy, diet structure, and lifestyles [22,23,24]. Indeed, survival strategies are most important for wild populations with low energy intake and high energy consumption in winter.…”
Section: Discussionmentioning
confidence: 99%